Influence of the spacer region between the Shine–Dalgarno box and the start codon for fine‐tuning of the translation efficiency in Escherichia coli. Issue 4 (23rd March 2020) - Komarova, Ekaterina S.; Chervontseva, Zoya S.; Osterman, Ilya A.; Evfratov, Sergey A.; Rubtsova, Maria P.; Zatsepin, Timofei S.; Semashko, Tatiana A.; Kostryukova, Elena S.; Bogdanov, Alexey A.; Gelfand, Mikhail S.; Dontsova, Olga A.; Sergiev, Petr V.
Summary: Translation efficiency contributes several orders of magnitude difference in the overall yield of exogenous gene expression in bacteria. In diverse bacteria, the translation initiation site, whose sequence is the primary determinant of the translation performance, is comprised of the start codon and the Shine–Dalgarno box located upstream. Here, we have examined how the sequence of a spacer between these main components of the translation initiation site contributes to the yield of synthesized protein. We have created a library of reporter constructs with the randomized spacer region, performed fluorescently activated cell sorting and applied next‐generation sequencing analysis (the FlowSeq protocol). As a result, we have identified sequence motifs for the spacer region between the Shine–Dalgarno box and AUG start codon that may modulate the translation efficiency in a 100‐fold range. Abstract : Understanding the principles that determine mRNA translation efficiency is of primary value for deciphering translational control of gene expression and for optimization of protein synthesis in biotechnology. In this work we combined Flowseq method with randomization of a region within the spacer between the Shine‐Dalgarno box and AUG start codon to decipher an influence of this mRNA part on translation efficiency.